Linguistic and acoustic analysis of voice disguise by impersonators - Talal Amin (Nanyang Technological University, 2015)
Human voices are distinct and rich with information such as the age, gender, emotional state and identity of the speaker. Voice impersonators possess a great deal of flexibility over their voices which allows them to imitate various people or characters. The question as to how impersonators are able transform their voices and what linguistic and acoustic parameters they rely on is still relatively unexplored. Understanding how they are able to transform their voices holds the key for many applications, such as, speaker recognition, voice transformation, voice disguise detection and speech coding etc.